A Thermodynamics Study on the Tetrahydrofuran Effect in Exfoliated Graphite Nanoplatelets and Activated Carbon Mixtures at Temperatures between 293.15 and 308.15 K. (29th March 2018) - Sirbu, Florinela; Ion, Alina Catrinel; Capra, Luiza; Ion, Ion
Abstract : A thermodynamics study on exfoliated graphite nanoplatelets dispersed in tetrahydrofuran in comparison with activated carbon dispersed in same solvent was realised. The refractive index, speed of sound, and density of diluted mixed binary solutions of exfoliated graphite nanoplatelets and activated carbon in tetrahydrofuran were measured between 0 and 100 kg·m −3 with composition step of 20 kg·m −3 and at temperatures from 293.15 to 308.15 K and at normal pressure. The isentropic compressibility, acoustic impedance, specific refraction, relaxation strength, and space-filling factor have been evaluated for six concentrations, at four different temperatures for each system. The identified possible molecular interactions between the edges and the surface of exfoliated graphite nanoplatelets and tetrahydrofuran molecules, which include modifications in the structure of exfoliated nanostructured materials in tetrahydrofuran solvent and the influence of the temperature, and of the solute concentration have been calculated based on the obtained experimental values.